Peran Kepemimpinan Kepala Madrasah dalam Manajemen Lembaga Pendidikan - Nada Rahmah, Alisa Qothrun; Fuadah; Shubhan Hudzaifa, Muhammad; Tamsikuddin; Dzuriyat, Masduki (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
Education is one part of the human development factor; through education the hope is that there will be changes that occur so that it can provide prosperity for the Indonesian people. To overcome the problems of education that occur, it requires a transformation factor that can be done by the leader. In educational institutions, namely principals who have a role in controlling, organizing, generating enthusiasm and conveying information. This research will use a qualitative method with a case study design, which uses interviews and observation instruments. The data analysis technique uses discourse analysis. The role of the principal in institutional management is very important, because the principal is a support for the implementation of educational programs. Through setting goals that will root the planning of several programs in addition to learning. The principal at MTs Nurul Hayah starts at the beginning of the new school year together with teachers and other educational staff to formulate this matter which affects organizational relations. In the implementation of each program and learning in this case is also carried out through the supervision of the principal as a supervisor who will later obtain data to improve the shortcomings of the program. This improvement is carried out through evaluation meetings between principals, teachers and other education staff in order to improve the quality of education. Apart from these several stages, the principal also motivates teachers and other teaching staff to develop competencies and improve facilities in supporting learning activities in order to provide a good environment. This research was conducted to find out a description of the role of the principal in institutional management, based on this this research needs to be developed from time to time because there are differences that can affect the role of the principal from time to time.